Psychosocial assessment tools for use before transplantation are predictive of post-operative psychosocial and health behavior outcomes: a narrative review of the literature - Thode, Sorin; Perry, Keith; Cyr, Samuel; Ducharme, Anique; Puissant, David; Brouillette, Judith (Frontiers in Transplantation, 2023)
Introduction In end-stage diseases, transplantation may be necessary. The limited number of donors led to the development of several pre-transplant psychosocial assessment tools. We summarized the predictive value of these tools before solid-organ transplantation. Methods The PRISMA search strategy and the MEDLINE database were used to review the literature. From 1050 records, we found thirteen studies using four different scales (Millon Behavioral Health Inventory, Psychosocial Assessment of Transplant Candidates, Stanford Integrated Psychosocial Assessment for Transplantation [SIPAT], and Transplant Evaluation Rating Scale [TERS]). Results TERS and MBHI were associated with the highest number of positive studies concerning pre-transplant scores and primary outcomes. Psychosocial scales predict in a systematic way psychosocial and health behavioural outcomes, but generated mixed results for mortality and rejection. Discussion This narrative review underlines the need for multidisciplinary evaluation and well-conducted clinical trials to assist transplant teams in utilizing psychosocial evaluation effectively during evaluation of candidates.